Sustainability reports and integrated reports: Their importance in decision-making and their relation to long-term performance in Latin American banks - Cohen, Natalia (2020)
Fil: Cohen, Natalia. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.